2019
DOI: 10.1371/journal.pcbi.1007456
|View full text |Cite
|
Sign up to set email alerts
|

The folded X-pattern is not necessarily a statistical signature of decision confidence

Abstract: Recent studies have traced the neural correlates of confidence in perceptual choices using statistical signatures of confidence. The most widely used statistical signature is the folded X-pattern, which was derived from a standard model of confidence assuming an objective definition of confidence as the posterior probability of making the correct choice given the evidence. The folded X-pattern entails that confidence as the subjective probability of being correct equals the probability of 0.75 if the stimulus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Therefore, a substantial number of recent studies have searched for the folded X-pattern to empirically identify correlates of decision confidence (Braun et al, 2018;Fetsch et al, 2014;Herding et al, 2019;Lak et al, 2017;Sanders et al, 2016;Urai et al, 2017). However, it has been shown mathematically that the folded X-pattern is neither a necessary nor a sufficient condition for Bayesian confidence (Adler & Ma, 2018;Rausch & Zehetleitner, 2019b). The present study showed empirically that a second statistical pattern of confidence exists and can be used to identify correlates of confidence.…”
Section: Statistical Signatures Of Confidence?mentioning
confidence: 70%
See 2 more Smart Citations
“…Therefore, a substantial number of recent studies have searched for the folded X-pattern to empirically identify correlates of decision confidence (Braun et al, 2018;Fetsch et al, 2014;Herding et al, 2019;Lak et al, 2017;Sanders et al, 2016;Urai et al, 2017). However, it has been shown mathematically that the folded X-pattern is neither a necessary nor a sufficient condition for Bayesian confidence (Adler & Ma, 2018;Rausch & Zehetleitner, 2019b). The present study showed empirically that a second statistical pattern of confidence exists and can be used to identify correlates of confidence.…”
Section: Statistical Signatures Of Confidence?mentioning
confidence: 70%
“…However, the folded X-pattern can be misleading about confidence because Bayesian decision theory is compatible with other statistical patterns, too (Adler & Ma, 2018;Rausch & Zehetleitner, 2019b). In addition, in some tasks, confidence empirically increased with stimulus strength in correct trials and to a lesser degree in incorrect trials (Kiani, Corthell, & Shadlen, 2014;Rausch, Hellmann, & Zehetleitner, 2018;Stolyarova et al, 2019;van den Berg et al, 2016), a pattern we refer to as double increase pattern.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A given model and task structure makes specific predictions on the shape of three key signatures relating stimulus discriminability, choice and confidence. The predictions can vary depending on task design (Adler and Ma, 2018;Rausch and Zehetleitner, 2019), but the structure of our task follows the original predictions (Hangya et al, 2016). Additionally, in our task, the mice combined the information about reward size with the strength of sensory evidence to select an action (confidence, or uncertainty) ( Figure 1).…”
Section: Td Error Dynamics In Signaling Perceptual Uncertainty and Cumentioning
confidence: 99%
“…For these interrelations to qualify as 314 signatures of the computation of confidence, certain statistical conditions must be satisfied. Specifically, the 315 counterintuitive behavior of confidence during error trials (i.e., lower confidence for stronger evidence) is 316 expected only when there is no overlap between stimulus distributions, so the mapping between evidence and 317 correct choice is unambiguous (Adler and Ma, 2018), and the evidence guiding the choices does not contain 318 independent trial-by-trial information about its discriminability (Rausch and Zehetleitner, 2018). Critically, 319…”
Section: Confidence As Inherent To the Decision-making Process 306mentioning
confidence: 99%